Responses of the Northern Bering Sea and Southeastern Bering Sea Pelagic Ecosystems Following Record‐Breaking Low Winter Sea Ice - Janet T. Duffy‐Anderson; Phyllis Stabeno; Alexander G. Andrews III; Kristin Cieciel; Alison Deary; Edward Farley; Corey Fugate; Colleen Harpold; Ronald Heintz; David Kimmel; Kathy Kuletz; Jesse Lamb; et al. (Geophysical Research Letters)
Abstract Bering Sea sea ice during winter 2017–2018 was the lowest ever recorded. Ecosystem effects of low ice have been observed in the southeastern Bering Sea, but never in the northern Bering Sea. Observations in both systems included weakened water column stratification, delayed spring bloom, and low abundances of large crustacean zooplankton. Summer Cold Pool presence was extremely limited. Young walleye pollock production and condition were similar to prior warm years, though catches of other pelagic forage fishes were low. Summer seabird die‐offs were observed in the northern Bering Sea, and to lesser extent in the southeastern Bering Sea, and reproductive success was poor at monitored colonies. Selected bottom‐up responses to lack of sea ice in the north were similar to those in the south, potentially providing environmental indicators to project ecosystem effects in a lesser studied system. Results offer a potential glimpse of the broader Bering Sea pelagic ecosystem under future low‐ice projections.